Search for endophytic diazotrophs in barley seeds - Zawoznik, Myriam Sara (2014)
Eight endophytic isolates assigned to Pseudomonas, Azospirillum, and Bacillus genera according to pheno-genotypic features were retrieved from barley seeds under selective pressure for nitrogen-fixers. Genetic relationships among related isolates were investigated through RAPD. Six isolates displayed nitrogen-fixing ability, while all could biosynthesize indolacetic acid in vitro and showed no antibiosis effects against Azospirillum brasilense Az39, a recognized PGPR.